Implementation of Green Architectural Rules in the Design of The Griya Samadhi Vincentius Hall In Prigen Village, Pasuruan Regency, East Java Province - Evert Indrawan, Stephanus; Herry Purwoko, Gervasius; Noviyanto P. Utomo, Tri (Green Publisher Indonesia, 2022)
Griya Samadi Vincent is located in a cool highland, the temperature ranges from 20-24c. A beautiful and quiet area of approximately 6-7 hectares. There is a chapel room and a special indoor room that is usually used for meditation. The entire garden area can be used for outdoor meditation. In addition to the facilities for meditation, there are also several waste processing sites, organic plant nurseries, animal husbandry and the use of biogas as an energy source for the complex. So far, the Griya Samadi Vincentius complex has been managed by the Parish of the Church of the Nativity of the Blessed Virgin Mary, which is a partner of the contributors. So far, Parish, apart from being the manager of financing and maintenance, has also carried out complex developments in terms of the legality of licensing. Where one aspect of licensing is a Building Permit or IMB, in this case the environmental aspect is an important point in regional planning. Therefore, the contributors and the team will plan the building using the Green Architecture method in accordance with the Indonesian Green Building Council standards, namely: Appropriate Site Development, Indoor Air Health and Comfort, Water Conservation, Material Resources and Cycle and Buiding Environment Management.